2005
DOI: 10.3390/10101325
|View full text |Cite
|
Sign up to set email alerts
|

Facile Preparation of Peracetates and Per-3-bromobenzoates of α-Mono- and Disaccharides

Abstract: A simple and convenient method for the preparation of fully acetylated and (3-bromo)benzoylated α-monosaccharides and disaccharides through vigorous mechanical mixing of solid reactants on a high speed shaker is described. Using this technique a variety of α‑acylated sugars are prepared, including penta-O-acetyl-α-D-galactopyranose, penta-O-acetyl-α-D-glucopyranose, penta-O-acetyl-α-D-mannopyranose, octa-O-acetyl-α-lactose, penta-O-(3-bromo)benzoyl-α-D-galactopyranose, penta-O-(3-bromo)benzoyl-α-D-gluco-pyrano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…These alkynecarbohydrate derivatives were obtained using two different methods of acetylation. 48,49 For the glucose and galactose derivatives, D-glucose and D-galactose were subjected to peracetylation with NaOAc in acetic anhydride, and the compounds were prepared in moderate yields. For the mannose derivative, catalytic amounts of I 2 were used instead of NaOAc.…”
Section: Resultsmentioning
confidence: 99%
“…These alkynecarbohydrate derivatives were obtained using two different methods of acetylation. 48,49 For the glucose and galactose derivatives, D-glucose and D-galactose were subjected to peracetylation with NaOAc in acetic anhydride, and the compounds were prepared in moderate yields. For the mannose derivative, catalytic amounts of I 2 were used instead of NaOAc.…”
Section: Resultsmentioning
confidence: 99%
“…For comparison, per(3-bromo)benzoates of α-D-lactose, α-D-glucose, α-D-galactose, α-D-mannose and β-D-mannose [ 21 ] were heated with AlCl 3 at 110 °C. It was found that all of the anomeric acyl groups ( i.e.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the anomeric configuration for β-D-glucose and β-D-galactose derivatives have been inverted in the respective products, e.g., from β-D-glucose pentaacetate to 2,3,4,6-tetra- O -acetyl-α-D-glucopyranose. While α-D-glucose and α-D-galactose per(3-bromo)benzoates [ 21 ] also undergo a similar debenzoylation at the anomeric position, the original α-configuration is retained in the corresponding products. However, the debenzoylation of α-D-mannose per(3-bromo)benzoate affords 2,3,4,6-tetra- O -(3-bromo)benzoyl-β-D-mannopyranose, indicating the conversion of configuration at the anomeric position during the debenzoylation.…”
Section: Resultsmentioning
confidence: 99%
“…This can be explained only admitting a limited glycolytic activity of promotor. 1 H NMR spectra of lactoside indicated it to be the alpha anomer 3 [18].…”
Section: Resultsmentioning
confidence: 99%